Women's Political Communications: Assessing Leadership In Queen Safiatuddin In Aceh Darussalam In The 17th Century - Marlinda Irawati (Inter Komunika, 2016)
Women leadership in the Kingdom of Aceh is inseparable from the prolonged debate because it is considered contrary to religious thought. Their appointment as the Queen cannot be separated because of the support of the party’s pro stronger, so it can be powerful in the kingdom of Aceh. Support group consists of several important clerics, most of the royal princess and common folk. Scholars who support the removal of the of the queen are Nuruddin Al-Raniri and Abdurrauf Al-Sinkili. This paper aims to: 1) know how Queen Safiatuddin leadership in the kingdom of Aceh on the 17th century; 2) reveals objectively political communication strategy Safiatuddin Queen in her coronation as Queen of the Kingdom of Aceh; and 3) Factors Queen On being in Charge Increase Kingdom of Aceh.